(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Objective: To assess the relationship between the effectiveness of treatment of year-round allergic rhinitis in children, taking into account the state of the initial vegetative tone of the body. Material and methods: The development includes 61 children with allergic rhinitis at the age of 7-15 years, of which 25 (41%) girls and 36 (59%) boys (main group). The control group consisted of 25 healthy children. Results: In children with perennial allergic rhinitis, a relationship was found between the initial vegetative tone of the body and the effectiveness of treatment. With a predominance of the parasympathetic orientation of the initial vegetative tone, a longer treatment was required and at a certain stage an increase in the dose of the drugs used. Conclusions: In children with perennial allergic rhinitis, there is a relationship between the results of pharmacotherapy and the initial autonomic tone of the body.